Effects of L-dopa and p-coumaric acid combination on oxidative stress, DNA damage, and mitochondrial apoptosis in neuroblastoma cells - Nebiye Pelin Turker; Elvan Bakar (Bangladesh Pharmacological Society, 2023)
This study aimed to investigate the effects of levodopa (L-dopa), p-coumaric acid, and combinations in the neuroblastoma (N1E-115) cell. L-dopa and L-dopa plus p-coumaric acid group caused oxidative stress by increasing 12.5 and 3.7-fold in superoxide dismutase gene, 11.5 and 4.8-fold increase in catalase gene, respectively. In L-dopa and L-dopa plus p-coumaric acid application, p21 gene expression increased 1.3-fold and 3.2-fold, and the cell cycle stopped in the G1 phase in response to stress in the treatment groups. In the application of L-dopa plus p-coumaric acid to N1E-115 cells, the BCL-2 gene, which is an apoptosis inhibitor, was suppressed and the BAX gene increased 13-fold compared to the control. As a result, it was determined that the cytotoxic effect of L-dopa plus p-coumaric acid application was less than the individual application of the substances, and p-coumaric acid had an inhibitory effect on L-dopa-induced stress.